EFL Students’ English Listening Comprehension Problem: A study of English Teacher Education Program - Zur, Sarjaniah (Advances in Social Sciences Research Journal, 2020)
Listening comprehensively is one of the way to build EFL students’ Listening skill, however, they still got problem in different phase of listening. The aimed of the study to identified the listening comprehension problem of EFL students during take English teacher program, the data was collected from Muhammadiyah university students in Kendari. This descriptive study used the listening comprehension problem questionnaire. The result of the study showed that the students still got difficulty in all three phases of listening problem, they are perception, parsing and utilization, moreover, the highest problems was in perception problem. So this problem is highly influence their quality of listening skill. This findings are expected to be a good implication for the lecturer in designing course and listening teaching strategy.